Assessment of sex- and age-dependency of risk factors for intimal hyperplasia in heart transplant patients using the high resolution of optical coherence tomography. (1st July 2022) - Orban, Madeleine; Dietl, Markus; Dischl, Dominic; von Samson-Himmelstjerna, Patrick; Neubarth-Mayer, Janina; Strüven, Anna; Tengler, Anja; Jakob, Andre; Fischer, Marcus; Rizas, Konstantinos; Petzold, Tobias; Orban, Martin; et al.
Abstract: Background: Intimal hyperplasia in cardiac allograft vasculopathy (CAV IH ) is limiting survival in pediatric and adult patients after heart transplantation (HTx). Analysis of risk factors for CAV IH using the high resolution of intracoronary optical coherence tomography (OCT) is scarce, particularly in children, and recommendations for CAV prevention are largely based on data obtained in adults. Whether the predictive value of risk factors is age- or sex-dependent is unknown. Methods and results: We used OCT to test the age- and sex-dependency of established risk factors regarding pathological CAV IH in a cohort of 102 pediatric and adult HTx patients (35% <18 years, 69% male). Modifiable parameters such as lipid values, and the diagnoses of dyslipidemia and diabetes showed age- and sex-dependent differences. Regarding CAV IH, receiver-operating characteristic analysis showed that LDL-c was relevant only in female patients (area under the curve [AUC] 0.79, p = 0.007), and total cholesterol in female (AUC 0.81; p = 0.004) and pediatric patients (AUC 0.73, p < 0.05). The association of dyslipidemia with CAV IH was stronger in adult (odds ratio [OR] 6.33) than in pediatric patients (OR 5.00) and in women (OR 6.00) than in men (OR 4.57). Diabetes was associated with CAV IH only in women (OR 11.25). Conclusion: In our cohort, modifiable risk factors, particularly total cholesterol and dyslipidemia, had a different impact depending on age and sex. Targeting risk factors in selected patients might improve individual CAV IH prevention. Highlights: Cardiac allograft vasculopathy (CAV) limits survival after heart transplantation. Intimal hyperplasia in intracoronary imaging (CAV IH ) is a main determinant of CAV. Whether the predictive value of risk factors is age- or sex-dependent is unknown. Diabetes and dyslipidemia had a different impact on CAV IH depending on age and sex. Total cholesterol was relevant regarding CAV IH only in women and children.